Systematic Literature Review: Buddhisme, Entrepreneur And SMEs - Herman Herman; Sopiah Sopiah (Jurnal Manajemen Riset Inovasi, 2023)
Today Buddhism contributes ideas based on theory and practice for Buddhist entrepreneurs. The purpose of this research is how the characteristics of buddhist entrepreneur in running an UKM. The research method used by researchers is SLR. The results of the study show that Buddhist entrepreneurs place more emphasis on ideology and religious beliefs in implementing entrepreneurship and running their UKM. The main principle in the development of UKM which continues to be used as a guideline is that the business that is carried out does not hurt, harm, and deceive other people or other creatures.